A Model of Factors Controlling the Financial Well-being of Earners in Northeastern Thailand - Tiwasasit, Atit; Chutivong, Naratip; Vongchavalitku, Bussaya; Ponklang, Pittaya (Hatyai Academic Journal, 2021)
This research examines the influence of personal factors regarding financial status, socialization, financial literacy, financial self-efficacy, and financial behavior on financial well-being and studies the causal relationship between factors that control the financial well-being of the earners. The application of two-stage sampling obtained a cluster of 506 income earners who are income earners registered in the social security registration system of the Northeastern region. The data were analyzed using structural equation modeling. The results show that financial behavior has a direct impact on financial well-being. Other indirect influential factors on financial well-being, with respective levels of significance, include financial behavior, financial literacy, and socialization. It is further revealed that financial literacy and financial self-efficacy have a significant direct impact on financial behavior. The model of factors controlling the financial well-being of the income earners fits with the empirical data. The results suggest that financial literacy and financial self-efficacy can provide desirable financial behavior which can lead to good financial well-being. Therefore, the government and private sectors should support and promote financial literacy to help income earners to have good financial well-being. The promotion is to help to build a financial habit of saving, investing, and ensuring financial risk among the earners including channels to access the financial knowledge with ease and accuracy.